2021
DOI: 10.1021/acs.jafc.1c04482
|View full text |Cite
|
Sign up to set email alerts
|

Dairy Processing Affects the Gut Digestion and Microecology by Changing the Structure and Composition of Milk Fat Globules

Abstract: Milk fat globules (MFGs) are the major source of energy for infants' dietary intake. In this study, the effects of changes in the structure and composition of MFG after dairy processing on lipolysis and immune regulation were investigated. Pasteurized MFG tends to form protein aggregates to prevent lipolysis. However, the aggregate is rich in neutrophil degranulation products, which are effective in killing pathogens. Homogenized MFG has the lowest hydrolysis rate due to the reconstituted antilipase barrier an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The decrease in the lipolysis degree of P‐HMFAE is mainly related to protein denaturation caused by heat treatment. Studies have shown that denatured milk proteins can form protein aggregates, hinder the interaction between lipase and internal triglycerides core, and limit the fat hydrolysis of lipid droplets 17 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The decrease in the lipolysis degree of P‐HMFAE is mainly related to protein denaturation caused by heat treatment. Studies have shown that denatured milk proteins can form protein aggregates, hinder the interaction between lipase and internal triglycerides core, and limit the fat hydrolysis of lipid droplets 17 …”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that denatured milk proteins can form protein aggregates, hinder the interaction between lipase and internal triglycerides core, and limit the fat hydrolysis of lipid droplets. 17 After pre-digestion in the gastric phase, fat of HMFAEs hydrolyzed rapidly in the intestinal phase. After 30 min of intestinal digestion, the lipolysis degree of HM, HMFAE, P-HMFAE, and S-HMFAE reached 45.89%, 46.32%, 44.55%, and 42.89%, respectively.…”
Section: Lipolysis Degreementioning
confidence: 99%
See 1 more Smart Citation
“…The separation of phospholipid antioxidant components is likely due to changes in milk fat structure caused by dairy processing (Yao et al ., 2015). PE is located within milk fat globules, and heat treatment promotes the formation of milk fat aggregates and causes PE to become embedded (Zhou et al ., 2021). In contrast, PC and SM are mainly located in the outer barrier of milk fat globules.…”
Section: Resultsmentioning
confidence: 99%
“…Fat‐soluble antioxidants in skimmed milk will be greatly lost, especially α‐tocopherol and vitamin A, which are concentrated in low melting point milk fat (Khan et al ., 2019). In addition, heating and homogenisation treatment have a remarkable effect on the loss of natural antioxidants, protein degradation, unfolding and formation of heat‐induced antioxidants or pro‐oxidants (Dias et al ., 2020; Zhou et al ., 2021). Thus, milk processing can affect TAC levels in various ways.…”
Section: Introductionmentioning
confidence: 99%